Enhancing resilient and nutritious forage varieties in Meru, Isiolo, and Tharaka Nithi counties - Nduah, Alex; Ogutu, Liz; Nzuki, Esther; Muthomi, Fredrick; Abucheli, Grace (2024)
This report examines the AICCRA project's efforts to enhance livestock productivity in Kenya’s arid and semi-arid lands (ASALs) by promoting drought-tolerant and high-nutrition forage varieties like Brachiaria and Panicum. On-farm trials and community demonstrations have supported farmers in learning how to grow and utilize the improved forage varieties compared to native grasses, reduce feed costs, and boost soil health. The project also established farmer capacity-building initiatives and seed value chains to promote sustainable adoption of the forages and economic benefits of livestock production in the ASALs.